Doctoral Student Reading and Writing: Making Our Processes Visible - Doyle, Melanie; Caissie, Chantelle (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2024)
Reading and writing are core components of what it means to be a doctoral student. Although reading and writing are known to be discursive, socialized practices, doctoral programs often focus on the output of these practices and position reading and writing as generic, universal skills. Through collaborative self-study, we sought to examine our reading and writing processes and see what we could learn as doctoral students by making these processes visible. From our analysis, we discovered that understanding our reading and writing processes enabled us to use effective reading and writing strategies; revealed the benefits of blurring personal-professional boundaries; and contributed to shaping our identity as emerging scholars. We conclude that supporting doctoral students to examine their personalized reading and writing processes, opposed to solely focusing on output, can support them to look inward, locate meaning within themselves, and recognize the multiplicity in what it means to read and write at the doctoral level.